Medication Knowledge Among Older Adults Admitted to Home Care in Ontario During 2012–2013. Issue 3 (May 2018) - Sears, Kim; Woo, Kevin Y.; Almost, Joan; Wilson, Rosemary; Frymire, Eliot; Whitehead, Marlo; VanDenKerkhof, Elizabeth
Abstract : Background: Medication use among Canadian seniors is widespread and increases with the number of comorbidities. Limited evidence exists on medication knowledge among seniors, especially in home care. Purpose: The purpose of this retrospective cohort study was to describe medication knowledge and ability to take medication among seniors admitted to home care in Ontario. Results: Ten percent had little or no knowledge of what medication to take ( n = 1, 389/14, 004) or an understanding of the purpose of their medications ( n = 1, 396/14, 004). Increasing numbers of medications prescribed was associated with decreased knowledge of medications. The strongest predictor of limited knowledge and ability to take medication was dementia (odds ratio > 5.0). Discussion: Among Ontario seniors living at home, knowledge about medications decreases as the number of medications increases. Therefore, this group may be at high risk of medication errors. Conclusion: Better systems are required to allow healthcare professionals to review with patients, any medications with patients and caregivers, to assist in addressing the decreased knowledge of medications. Such a system would provide the capacity to target those individuals at high risk for a medication error, as well as the medications and drug–drug interactions that seem most likely to be harmful among older adults.